Quantitative comparison of hemodynamic parameters from steady and transient CFD simulations in cerebral aneurysms with focus on the aneurysm ostium. (10th April 2014) - Karmonik, C; Diaz, O; Klucznik, R; Grossman, R G; Zhang, Y J; Britz, G; Lv, N; Huang, Q
Abstract : Objective: To quantitatively compare hemodynamics simulated with steady-state and transient computational fluid dynamics (CFD) simulations in cerebral aneurysms with single inflow, with focus at the aneurysm ostium. Methods: Transient and steady-state CFD simulations were performed in 10 cerebral aneurysms. Distributions and average values for pressure, helicity, vorticity, and velocity were qualitatively compared at proximal and distal parent artery locations, at the ostium plane, and in the aneurysm, and scaling factors between the two kinds of simulations were determined. Relative inflow and outflow areas at the ostium were compared, as were average inflow and outflow velocities. In addition, values for the pressure-loss coefficient (PLC), a recently introduced parameter to assess aneurysm rupture risk, were compared for both kinds of simulation. Results: Distributions of hemodynamic parameters had a similar shape but were lower for transient than for steady-state simulations. Averaged scaling factors over cases and anatomical locations showed differences for hemodynamic parameters (0.485±0.01 for pressure, 0.33±0.02 for helicity, 0.58±0.06 for vorticity and 0.56±0.04 for velocity). Good agreement between ratios of inflow and outflow areas at the aneurysm ostium was obtained (Pearson correlation coefficient >0.97, p<0.001) and for the PLC (linear regression slope 0.73±0.14, R 2 =0.75). Conclusions: Steady-state simulations are a quick alternative to transient simulation for visualizing and quantifying inflow and outflow areas at the aneurysm ostium, potentially of value when planning flow diverter treatment and for quantifying the PLC, a potential indicator of aneurysm rupture.